Eksplorasi Praktik Kawin Culik “Merarik” di Kecamatan Wanasaba, Lombok Timur - Sulpa Indra Mahruni; Abbas Sofwan Matlail Fajar (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – This study aims to describe and analyze the intriguing practices conducted by the Sasak community in the Wanasaba District of East Lombok Regency. Methods – This study adopts a case studies with qualitative approach, utilizing data collection techniques through participatory observation, in-depth interviews, and document analysis. Findings – The findings reveal the presence of diverse intriguing practices that constitute an integral aspect of Sasak people's life. These practices encompass elements of local culture, indigenous wisdom, and social interactions within the community. Moreover, the study identifies the repercussions of these practices on the cultural and environmental sustainability of the region. Research implications – The findings of this research offer valuable insights into understanding and appreciating the traditional practices of the Sasak people. They also serve as a foundation for developing policies that promote cultural and environmental sustainability in Wanasaba Sub-district. Top of Form Originality/value – Through these findings, valuable insights emerge, fostering a deeper understanding and appreciation of Sasak traditions. Moreover, they serve as a pivotal foundation for crafting policies aimed at nurturing cultural preservation and fostering environmental stewardship within the Wanasaba Sub-district and beyond.